1993
DOI: 10.1016/0014-5793(93)81766-s
|View full text |Cite
|
Sign up to set email alerts
|

Purification and sequence determination of heat‐stable enterotoxin elaborated by a cholera toxin‐producing strain of Vibrio cholerae O1

Abstract: Four molecular species of heat-stable enterotoxins elaborated by a cholera toxin-producing strain of Vibrio cholerae O1 were isolated from its culture supernatant. The amino acid sequence of one of the enterotoxins was determined to be Phe-Ile-Lys-Gln-Val-Asp-Glu-Asn-Gly-Asn-Leu-Ile-Asp-Cys-Cys-Glu-Ile-Cys- Cys-Asn-Pro-Ala-Cys-Phe-Gly-Cys-Leu-Asn with three intramolecular disulfide linkages. The other enterotoxins had shorter amino acid sequences in the N-terminal regions, but possessed the same sequence in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…This observation indicates that A-2 is the C-terminal fragment in Y-STb, but A-1 is not [13]. The amino acid sequence of A-1 was identical to that of a part (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) of the N-terminal amino acid sequence of the purified Y-STb, which is consistent with the data from FAB-MS and amino acid analysis ( Fig. 3 and Table 1).…”
Section: Sequence Determination Of Y-stbmentioning
confidence: 63%
See 1 more Smart Citation
“…This observation indicates that A-2 is the C-terminal fragment in Y-STb, but A-1 is not [13]. The amino acid sequence of A-1 was identical to that of a part (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) of the N-terminal amino acid sequence of the purified Y-STb, which is consistent with the data from FAB-MS and amino acid analysis ( Fig. 3 and Table 1).…”
Section: Sequence Determination Of Y-stbmentioning
confidence: 63%
“…An aliquot of each fraction was tested for toxicity in suckling mice and the active fractions were pooled. The fractions containing toxic materials were concentrated, dialyzed against distilled water, and then subjected to immunoaffinity chromatography using a monoclonal antibody (MAb), 2F, under conditions described previously [9]. The toxic fractions obtained by immunoaffinity chromatography were purified further by reversed-phase highperformance liquid chromatography (RP-HPLC) (see legend of Fig.…”
Section: Isolation Of Y-stbmentioning
confidence: 99%
“…The MED of T-2 was nearly identical to that of T-l, indicating that the conversion of Nterminal Gln to pGlu does not affect the enterotoxic activity. In ST molecules produced by V. cholerae O1, the molecules with the shorter N-terminal sequences showed more potent toxicities, and the MED of the largest one with 28 amino acid residues was ten times more than that of the smallest one with 17 amino acid residues [8]. In contrast, Y-STc was the most toxic in the ST family despite having the longest sequence.…”
Section: Toxicity Of Y-stcmentioning
confidence: 73%
“…3). The length of the secreted mature polypeptides ranges from only 17 amino acid residues for NAG-ST and O1-ST produced by E cholerae [6,8] sequences of Y-STc and the pro-form of Y-STa revealed that there is a sequence similarity of 49% (26 residues/53 residues) (Fig. 3).…”
Section: C-c-[e/d]-[l/i/v]-c-c-n-p-a :C-[a/t/f]-g-cmentioning
confidence: 99%
See 1 more Smart Citation